Nitric oxide function in plant biology: a redox cue in deconvolution. Issue 4 (10th March 2014) - Yu, Manda; Lamattina, Lorenzo; Spoel, Steven H.; Loake, Gary J.
<x xml:space="preserve">Abstract</x> <table-wrap position="anchor" orientation="portrait"> 1142 I. I. 1142 II. II. 1143 III. III. 1143 IV. IV. 1144 V. V. 1144 VI. VI. 1145 VII. VII. 1147 VIII. VIII. 1148 IX. IX. 1149 X. X. 1149 XI. XI. 1151 XII. XII. 1151 XIII. XIII. 1152 XIV. XIV. 1152 1153 References 1153 </table-wrap> Summary Nitric oxide (NO), a gaseous, redox‐active small molecule, is gradually becoming established as a central regulator of growth, development, immunity and environmental interactions in plants. A major route for the transfer of NO bioactivity is S‐nitrosylation, the covalent attachment of an NO moiety to a protein cysteine thiol to form an S‐nitrosothiol (SNO). This chemical transformation is rapidly emerging as a prototypic, redox‐based post‐translational modification integral to the life of plants. Here we review the myriad roles of NO and SNOs in plant biology and, where known, the molecular mechanisms underpining their activity.